Mitochondrial Ca2+ and ROS take center stage to orchestrate TNF-α–mediated inflammatory responses - Laura A. Dada; Jacob I. Sznajder (The Journal of Clinical Investigation, 2011)
Proinflammatory stimuli induce inflammation that may progress to sepsis or chronic inflammatory disease. The cytokine TNF-α is an important endotoxin-induced inflammatory glycoprotein produced predominantly by macrophages and lymphocytes. TNF-α plays a major role in initiating signaling pathways and pathophysiological responses after engaging TNF receptors. In this issue of JCI, Rowlands et al. demonstrate that in lung microvessels, soluble TNF-α (sTNF-α) promotes the shedding of the TNF-α receptor 1 ectodomain via increased mitochondrial Ca2+ that leads to release of mitochondrial ROS. Shedding mediated by TNF-α–converting enzyme (TACE) results in an unattached TNF receptor, which participates in the scavenging of sTNF-α, thus limiting the propagation of the inflammatory response. These findings suggest that mitochondrial Ca2+, ROS, and TACE might be therapeutically targeted for treating pulmonary endothelial inflammation.